Bacillus megaterium adapts to acid stress condition through a network of genes: Insight from a genome-wide transcriptome analysis. Issue 1 (December 2018) - Goswami, Gunajit; Panda, Debashis; Samanta, Ramkrishna; Boro, Robin; Modi, Mahendra; Bujarbaruah, Kamal; Barooah, Madhumita
Abstract RNA-seq analysis ofB .megaterium exposed to pH 7.0 and pH 4.5 showed differential expression of 207 genes related to several processes. Among the 207 genes, 11 genes displayed increased transcription exclusively in pH 4.5. Exposure to pH 4.5 induced the expression of genes related to maintenance of cell integrity, pH homeostasis, alternative energy generation and modification of metabolic processes. Metabolic processes like pentose phosphate pathway, fatty acid biosynthesis, cysteine and methionine metabolism and synthesis of arginine and proline were remodeled during acid stress. Genes associated with oxidative stress and osmotic stress were up-regulated at pH 4.5 indicating a link between acid stress and other stresses. Acid stress also induced expression of genes that encoded general stress-responsive proteins as well as several hypothetical proteins. Our study indicates that a network of genes aidB .megaterium G18 to adapt and survive in acid stress condition.